Privacy and personal data collection with information externalities - Choi, Jay Pil; Jeon, Doh-Shin; Kim, Byung-Cheol (Journal of public economics, 2019)
We provide a theoretical model of privacy in which data collection requires consumers' consent and consumers are fully aware of the consequences of such consent. Nonetheless, excessive collection of personal information arises in the monopoly market equilibrium which results in excessive loss of privacy compared to the social optimum. The main mechanism for this result is information externalities and users' coordination failure in which some users' decision to share their personal information may allow the data controller to infer more information about non-users. We also show that the emergence of data brokerage industry can facilitate the collection and monetization of users' personal data even in a fragmented market where no individual website has incentives to do so independently due to scale economies in data analytics. We discuss policy implications of our analysis in light of the recent EU General Data Protection Regulation (GDPR).